2012
DOI: 10.1590/s1415-47572012005000072
|View full text |Cite
|
Sign up to set email alerts
|

Biometric variability of goat populations revealed by means of principal component analysis

Abstract: The aim was to analyze variation in 12 Brazilian and Moroccan goat populations, and, through principal component analysis (PCA), check the importance of body measures and their indices as a means of distinguishing among individuals and populations. The biometric measurements were wither height (WH), brisket height (BH) and ear length (EL). Thorax depth (WH-BH) and the three indices, TD/WH, EL/TD and EL/WH, were also calculated. Of the seven components extracted, the first three principal components were suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…Diversity in morphostructural traits were reported in goats by Brown et al (1973), Odubote (1994), Jordana et al (1995), Rey et al (1995), Herrera et al (1996), Jimcy (2007) and Verma et al (2009). Pires et al (2012) explained that the use of graphical representation of PCA values allowed to distinguish between genetic groups of goats in Brazilian and Moroccan goat populations.…”
Section: Resultsmentioning
confidence: 99%
“…Diversity in morphostructural traits were reported in goats by Brown et al (1973), Odubote (1994), Jordana et al (1995), Rey et al (1995), Herrera et al (1996), Jimcy (2007) and Verma et al (2009). Pires et al (2012) explained that the use of graphical representation of PCA values allowed to distinguish between genetic groups of goats in Brazilian and Moroccan goat populations.…”
Section: Resultsmentioning
confidence: 99%
“…Crespa goats are small (morphometric data are shown in S1 Figure and S2 Table), with a typical white, silky, and curly fleece, which distinguishes them from all other goat breeds in the region [for a comparison with the body sizes of Saanen, Alpine, Anglo-Nubian, and Boer breeds, see Agraz-Garcia (1976), Pesmen and Yardimci (2008), and Pires et al (2012)]. They are phenotypically uniform and very similar in size (e.g., in wither height, chest depth, and body length) to the Angora, in particular, when compared to data from Angora herds found in the mid-20th century at Lalahan, near Ankara, Turkey (Bilgemre, 1953).…”
Section: Goats and Samplesmentioning
confidence: 99%
“…In addition to the Angora, which originated in Turkey and is the only breed that produces mohair (Shelton, 1993) (a fiber only slightly coarser than cashmere), other European breeds were introduced into the region to increase either milk production (e.g., Alpine and Saanen) or both milk and meat (e.g., Anglo-Nubian) (Pires et al, 2012). The South African Boer was introduced later to improve meat production.…”
Section: Introductionmentioning
confidence: 99%
“…The total variance values indicate that the first ten major components accounted for 85.35% of the total data variation. Pires et al (2012) evaluated the morphometric variability of dairy goats and found that the first three major components accounted for about 99.51% of the total data variation.…”
Section: Resultsmentioning
confidence: 99%